Knowledge and Practice of Healthcare Workers Regarding Patients' Physical Safety at Mbarara Regional Referral Hospital. - Diana Nakayenga; Jane Kasozi Namagga (Student's Journal of Health Research, 2021)
Background: Patients' physical safety is one of the most crucial elements considered during the provision of patient-centered healthcare. It entails the prevention of physical harm to a patient. The overall purpose of this study was to describe the knowledge and practice of healthcare workers regarding patients' physical safety. The aims of the study were to determine the knowledge of health workers regarding patients' physical safety and describe the practice of health workers regarding patients' physical safety at Mbarara Regional Referral Hospital. Methodology: The target sample for the study was 70 respondents and these were selected using convenience sampling because of the ease in assembling the sample. Frequencies and percentages were conducted to analyze quantitative data using SPSS version 25. Results: The study showed most healthcare workers had knowledge about patient's physical safety, most got this knowledge from their colleagues on the ward and they always considered the mental health status while assessing the risk of falls daily. Conclusion and recommendations: The study concluded that in stressful and often hazardous work environments, the health and safety of patients are the first priority. The study, therefore, recommends that the health care sector must make a fundamental shift to equate worker safety with patient safety. It must also make this shift a strategic priority if it is to deliver exemplary patient care and ensure the health and safety of patients. Failure to do so puts the sector at risk and makes it vulnerable to crises.